UPAYA MENINGKATKAN KUNJUNGAN WISATAWAN DI KERATON RATU BOKO - , ADITYA YUNIADI R ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Diploma Course Vocational School of Tourism University of Gajah Mada. This final report examines the efforts made to increase the number of tourist arrivals in Ratu Boko. This study aims to answer the question in this research, which is what the efforts made by PT. Taman Wisata Candi Borobudur, Prambanan and Ratu Boko Boko unit to attract visitors so that the number of tourist arrivals in the Boko increased. Writing of this report presented to obtain a qualitative description of various efforts made to attract tourists to the Ratu Boko Palace. Methods of data collection using observation, interviews, document studies and literature. The data obtained were then analyzed qualitatively and presented descriptively. The results showed that the number of visits in less than Boko Prambanan. The work done is by promotion to a variety of print media, brochures, and so invite the shuttle package tour players interested in visiting Kraton Ratu Boko. The conclusion can be drawn that the PT. Taman Wisata Candi Borobudur, Prambanan and Ratu Boko has made great efforts to increase the number of tourists visiting Ratu Boko and the result of each year the number of visits increased from shuttle package.